1997
DOI: 10.1007/s004410050918
|View full text |Cite
|
Sign up to set email alerts
|

Light-/dark-induced changes in rhabdom structure in the retina of Octopus bimaculoides

Abstract: We examined rhabdom structure and the distribution of filamentous actin in the photoreceptor outer segments of the retina of Octopus bimaculoides. Animals were dark- or light-adapted, fixed, embedded and sectioned for light and electron microscopy. Statistical analyses were used to compare relative cross-sectional areas of rhabdom microvilli and core cytoplasm within and between the two lighting conditions. Dark-/light-adapted rhabdoms were also prepared for confocal laser scanning microscopy and labeled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…The membrane of each rhabdomere microvillus contains rhodopsin and signal transduction proteins necessary to process the visual signal after light absorption by rhodopsin as well as a core of actin filaments and accessory proteins (Robles et al 1995, De Velasco et al 1999). As mentioned, the rhabdoms increase in size in the dark, by the addition and lengthening of the rhabdomere microvilli, and decrease in the light by the disassembly and shortening of the same microvilli (Torres et al 1997). …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The membrane of each rhabdomere microvillus contains rhodopsin and signal transduction proteins necessary to process the visual signal after light absorption by rhodopsin as well as a core of actin filaments and accessory proteins (Robles et al 1995, De Velasco et al 1999). As mentioned, the rhabdoms increase in size in the dark, by the addition and lengthening of the rhabdomere microvilli, and decrease in the light by the disassembly and shortening of the same microvilli (Torres et al 1997). …”
Section: Resultsmentioning
confidence: 97%
“…Rhabdom cross-sectional areas increase in size in the dark and diminish in the light (Torres et al 1997). This increase can be explained by either the addition of new microvilli or increase in size of microvilli already present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contraction and elongation of cone cells in fish eyes are regulated by actin and microtubles, respectively[16]. Rhabdom size of octopus[15] and some terrestrial isopods, fly, and crayfish are also controlled by actin filaments[13,14,27]. The morphological change of the ocelloid of Erythropsidinium in response to light resembles the alteration in size of rhabdomere cells of some cephalopods and arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising, as molluscan systems have shown potential for study of basic visual processes, physiology of vision, development of the visual system, and evolution. For example, past work (Robles et al 1995, Torres et al 1997 has shown that cytoskeletal organization of photoreceptor cells is regulated by the state of light-and dark-adaptation in cephalopod eyes. It is known that some disease states in the human retina, such as macular degeneration, affect cytoskeletal development and organization (Eckmiller 2004).…”
Section: Molluscs As "Non-traditional" Model Organisms For Studying Tmentioning
confidence: 99%